Local surface conductivity of transition metal oxides mapped with true atomic resolution. Issue 24 (11th June 2018) - Rodenbücher, C.; Bihlmayer, G.; Speier, W.; Kubacki, J.; Wojtyniak, M.; Rogala, M.; Wrana, D.; Krok, F.; Szot, K.
Abstract : Local-conductivity atomic force microscopy with atomic resolution reveals that the surface conductivity of slightly reduced transition metal oxides such as TiO2 and SrTiO3 is confined to conductance paths on the nanoscale. Abstract : The introduction of transition metal oxides for building nanodevices in information technology promises to overcome the scaling limits of conventional semiconductors and to reduce global power consumption significantly. However, oxide surfaces can exhibit heterogeneity on the nanoscale e.g. due to relaxation, rumpling, reconstruction, or chemical variations which demands for direct characterization of electronic transport phenomena down to the atomic level. Here we demonstrate that conductivity mapping is possible with true atomic resolution using the tip of a local conductivity atomic force microscope (LC-AFM) as the mobile nanoelectrode. The application to the prototypical transition metal oxide TiO2 self-doped by oxygen vacancies reveals the existence of highly confined current paths in the first stage of thermal reduction. Assisted by density functional theory (DFT) we propose that the presence of oxygen vacancies in the surface layer of such materials can introduce short range disturbances of the electronic structure with confinement of metallic states on the sub-nanometre scale. After prolonged reduction, the surfaces undergo reconstruction and the conductivity changes from spot-like to homogeneous as a result of surface transformation. The periodic arrangement of the reconstruction is clearly reflected in the conductivity maps as concluded from the simultaneous friction force and LC-AFM measurements. The second prototype metal oxide SrTiO3 also reveals a comparable transformation in surface conductivity from spot-like to homogeneous upon reduction showing the relevance of nanoscale inhomogeneities for the electronic transport properties and the utility of a high-resolution LC-AFM as a convenient tool to detect them.